Contested comitology? The overlooked importance of the EU Commission. Issue 6 (3rd June 2022) - Finke, Daniel; Hansen, Jens Blom
ABSTRACT: Composed of member states representatives, the comitology committees are watchdogs that limit the Commission's discretion in implementing EU law. Yet, these watchdogs appear very tame, eventually adopting all measures proposed by the Commission. This apparent consensus clashes with the institutional skirmishes that characterize the negotiations over the design of the comitology system and the delegation provisions in daily EU legislation. In this article, we offer a quantitive study of the interaction between the Commission and the comitology committees. Using latent class analysis, we identify two worlds of comitology. Dealing with technically complex, non-salient cases, the first world is characterized by high specialization and hardly any dissenting comitology votes. By contrast, the second world includes politically salient cases, mobilizing high levels of expertise in the Commission and about 35% dissenting comitology votes. In the second part, we zoom in on this second world, studying under which conditions dissenting votes appear.